The preliminary study of cell membrane stability of Pleurotus ostreatus (Jacq. ex Fr.) P. Kumm strains related to the production of fruiting body - Hidayat, G. A.; Saskiawan, I.; Ekowati, N. (International Journal of Agricultural Technology, 2019)
One of the most widely cultivated edible mushroom in Indonesia is Pleurotus ostreatus (Jacq. Ex Fr.) P. Kumm or commonly called “white oyster mushroom”. The growth and fruit body formation of P. ostreatus is influenced by environmental factors, especially temperature. High temperature tended to cause disadvantages because it can reduce the rate of mushroom growth. Heat stress affects cell membrane function. The increased permeability and leakage of electrolyte out of the cell has been used as a measure of cell membrane stability (CMS) and as a screen test for stress tolerance. CMS can be done by measuring cell’s relative injury (RI). Based on result, the lowest damage was found in InaCC F10 strain (31,21% RI), while the highest damage was found in InaCC F209 strain (52,98%). Result stated that different types of P. ostreatus strains significantly affected the stability of the fungal cell membrane. Further test stated that InaCC F10 [RI=31,21(a)] and InaCC F216 [RI=32,11(a)] strains were the same effect and the lowest damage levels, while InaCC F196 [RI=47,18(c)] and InaCC F209 [RI=52,98(c)] strains were the same effect, but the highest damage levels. The biological efficiency (BE) was observed to determine the productivity of P. ostreatus strains. Result stated that different types of P. ostreatus strains significantly affected the productivity of mushroom. Further test stated that InaCC F10 was the highest productivity [BE=21.62% (c)], while the lowest productivity was found in InaCC F196 strain [BE=11.10%(a)] and InaCC F131 strain [BE=12,46%(a)].